Enhancing Issue Management through the Employment of Inspection Technique: An Experience Report in The Industry - Castro, Renata; Oliveira, Flavia; Rodrigues, Janderson; Tiago, Leonardo; Sousa, Cesar; Chaves, Lennon (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
The software industry has been adopting the concept of Global Software Development to release products quicker and with fewer costs, assuring quality by employing software testing techniques which are able to detect issues early. In this context, this paper presents an experience report performed at SIDIA Institute of Science and Technology between the years of 2020 and 2022, during which a process of issue management (IM) was developed to reduce the problems in the issue report, such as: lack of cohesion, absence of confirmation tests and long learning curve time of the testing team. In order to face these challenges, the IM process employs inspection techniques in order to improve the quality of reports, and then, increase its effectiveness, i.e., the number of valid issues. In addition, to support the IM process, it was created an onboarding phase, a template for issue reports and the monitoring of issues until the confirmation test. Through the implementation of this process, there was evaluated a total amount of 11002 issues report, and as a result, it was observed that the issues’ effectiveness rate was increased from to (raising by ) in the period in which this research was performed. In sequence, it was detected that around of issues had problems related to issue report writing. Furthermore, qualitative research revealed that of the interviewed testers consider the process effective. The authors hope that lessons learned described in this paper can contribute to the academic and industry communities by regarding the employment of inspection techniques to evaluate issue reports.